2017
DOI: 10.18006/2017.5(2).134.142
|View full text |Cite
|
Sign up to set email alerts
|

Influence of varying nitrogen levels on growth, yield and nitrogen use efficiency of hybrid maize (Zea mays)

Abstract: Present investigation was carried out at Natore Sugar Mills area, Natore, Bangladesh during 2014-15 to evaluate the growth and yield responses of hybrid maize varieties under different levels of nitrogen fertilization. Two hybrid maize varieties viz. BARI hybrid maize-7 and BARI hybrid maize-9 were tested under four nitrogen levels (N0= without external nitrogen supply, N1= 115 kg N ha -1 , N2= 230 kg N ha -1 , and N3= 345 kg N ha -1 ). All recommendations agronomic practices were used for both the , grain num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
4
5
0
2
Order By: Relevance
“…Nitrogen doses 180 kg ha -1 , 200 kg ha -1 and 220 kg ha -1 had a statistically similar number of rows per cob i.e., 14.27, 14.56 and 14.97 respectively (Table 3). Similar results were obtained by Majid et al, (2017), Gungula et al (2003), Waqas (2002), who found the increase in grain row per cob with the increase in N level.…”
Section: Effect On Numbers Of Rows Per Cobsupporting
confidence: 89%
See 1 more Smart Citation
“…Nitrogen doses 180 kg ha -1 , 200 kg ha -1 and 220 kg ha -1 had a statistically similar number of rows per cob i.e., 14.27, 14.56 and 14.97 respectively (Table 3). Similar results were obtained by Majid et al, (2017), Gungula et al (2003), Waqas (2002), who found the increase in grain row per cob with the increase in N level.…”
Section: Effect On Numbers Of Rows Per Cobsupporting
confidence: 89%
“…Whereas, Nitrogen dose of 160 kg ha -1 had the least cob diameter (4.10 cm) ( Table 3). A similar result was obtained by Majid et al (2017), who observed the highest cob diameter with the application of 225 kg N ha -1 . Similarly, Saleem et al (2017), Oktum and Oktern (2005) noted the significant increment in cob diameter with increasing level of Nitrogen.…”
Section: Effect On Diameter Of Cobsupporting
confidence: 87%
“…Further, application of 125 % or 100 % NPK increased cob length indicated that these hybrids respond for high level of nutrients. Results are in line with the findings of Majid et al (2017) and Patil et al (2018). Application of different nitrogen doses had significant influence the girth of cob in BARI hybrid maize-7 and BARI hybrid maize-9.…”
Section: Yield Componentssupporting
confidence: 93%
“…Thus there was increase in test weight. Similar results were reported by Majid et al (2017).Higher yield of maize hybrids viz., RCRMH-3 and RCRMH-2 was due to significantly superior growth and yield parameters viz., plant height, number of green leaves per plant, leaf area per plant, leaf area index, leaf area duration, total dry matter accumulation, cob length, cob girth, no. Of grains cob -1 and test weight.…”
Section: Yield Componentssupporting
confidence: 89%
See 1 more Smart Citation